RAGAM HIAS NISAN KOMPLEKS PEMAKAMAN RAJA KOTALAMA, KABUPATEN INDRAGIRI HULU, PROVINSI RIAU - - Rinaldi; Azmi Dwi Seffiani (Balai Arkeologi Sumatera Utara, 2019)
The cemetery of the King Kotalama complex is the Indragiri royal burial complex of the islamic-style period of Narasinga II. This study focused on the type of ornament that developed in the burial complex of the king of Kotalama. Decoration can provide information about the development of art culture during the reign of Narasinga II. The method used to answer these problems is through morphological analysis and stylistic analysis, in order to find out the types of decorations. The developing decoration shows that the community acculturates the old culture and the new culture. The ornamental variety consists of flora, geometric and calligraphy.